DAMPAK KERJASAMA INDUSTRI KREATIF INDONESIA-KOREA SELATAN DALAM UPAYA PENGEMBANGAN SEKTOR EKONOMI KREATIF DI INDONESIA - ", Sagita; Yealta, Den (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Abstract            Nowadays global competition and the depletion of natural resources are encouraging most of the countries in the world to find the alterantive of economic matters that doesn’t depend on nature, one of the alternative is by switching the option to creative economy, which is an economic matter that based on creativity and intellectual abalities. Creative economy known as a concept which evolves and focuses on creativity as a main asset to  generate the economic growth and development. Creative Economy and Creative Industry in Indonesia was discussed and evolved since 2006. Up until now, the creative industry development efforts are continue to be made by Indonesian Government. One of the effort is by doing a cooperation with South Korea. Korea becomes such a phenomenon in the technology development and its culture which evolves rapidly in Asia for the recent decades, and it is able to do the effective development and culture strategy, which is by its creative industry.            This research used the descriptive analysis method, which means, a research method that describes occasions or occurences based on the actual on going datas and facts, to obtain an analysis about the effect of Indonesia and South Korea cooperation in the developmment of creative industrial sector in Indonesia. Researcher also used the literature study data accumulation technic, which means, an effort to find and collect the datas and informations based on reviews and references, whether it’s from text books, magazines, newspapers, articles, internets or documents about things that related to the case which researcher examined.            The cooperation of both countries was done in some of cooperation and program types, which amongst : the education training, the exchange of industry subject, and promoting both of the countries creative industry businesses. Besides trying on the creative subject’s quality development, investment increasing in oder to support the creative industry production is also one of the result that successfully achieved from this cooperation. However,  this cooperation is not fully effective because there are still some obstacles and also it still doesn’t obtain a stable result for both of the countries, in this case, South Korea still dominates the cooperation.Keywords : Cooperate, Creative Economy, Creative Industry, Indonesia, South Korea